REIMAGINING HUMAN RESOURCE: REDEFINE HUMAN RESOURCE MANAGEMENT PRACTICES FOR THE FUTURE - Riani, Dini (Jurnal Riset Bisnis dan Manajemen, 2024)
Digital transformation is changing the way organizations interact with customers, run operations, and recruit and manage human resources. As a result, conventional paradigms in human resource management must be re-examined to remain in line with the needs of this digital era which encourages HR to move from an administrative role towards providing added value through in-depth data analysis. This research aims to reimagine human resource management (HR) practices in facing future challenges. The research method used is a descriptive method from a mix method perspective. Stakeholders or leaders in the Company who show agreement on several components that require a re-description of HR, this is based on conditions that have occurred in the past 5 years which are supported by several conditions that have occurred and demands for technological change and the Company's achievements. The findings of this research rearticulating HR practices for the future is an important step for organizations that want to remain relevant and competitive. The adoption of a new paradigm in human resource management is a reflection of the organization's commitment to adaptability, innovation and sustainability in the face of inevitable changes in the world of work.